Modeling of Electrodialytic Desalination of Regenerated Water Effluent with Byproducts Recovery. - Paz-García, Juan Manuel; Olivares-Ligero, Elena; Cerrillo-González, María del Mar; Martinez-Salverri, María José; Rodríguez-Maroto, José Miguel; Villén-Guzmán, María Dolores (Jeonju National University, 2024)
Electrodialytic desalination (EDD) is a promising technique for wastewater treatment that leverages an electric field to drive ion movement through ion-exchange membranes, efficiently removing salts and other impurities from water. This method has been successfully employed to produce water suitable for drinking and agricultural purposes. Compared to traditional methods like reverse osmosis, EDD offers the advantages of lower energy consumption and reduced chemical usage. Namely, EDD has not the problem of the generation of high concentrated salty water produced in the reverse osmosis treatment. A model for EDD of brackish wastewater has been developed with the goal of reducing regenerated water conductivity to levels suitable for agricultural or recreative use in a single pass through a membrane system. Additionally, apart from generated the dilute stream, the cell design ensures that the separated ions generate valuable solutions in the auxiliary compartments. Specifically, a four-compartment cell has been conceptualized to prevent chlorine gas formation at the anode, instead producing either HCl or FeCl3 and NaOH-rich solutions along with the diluted stream. This innovative design enhances the efficiency and sustainability of the EDD process. FeCl3 and FeCl2 are typically used in wastewater for flocculation-coagulation in the primary and tertiary treatments. By means of a Fe0-based sacrifize anode, FeCl3 and FeCl2 can be produced during the EDD treatment and recuperated for direct use in the water treatment plant.
Keywords: Desalinización - Proceso de electrodiálisis; Electrodialytic remediation; Water treatment; Multyphisics modeling